Why are there Escalating Incidences of Confrontations in Nepali Hospitals? An Anthropological Critique - Dahal, Kapil (Molung Educational Frontier, 2020)
This article deals with the emerging phenomenon of confrontations and vandalism in hospitals in Nepal. It interrogates how far paternalism and commodification has become the feature of the Nepali health care sector and their interrelationships with each other. With the esoteric nature of medicine and different explanatory models of understanding illness episodes and healing outcomes, there is always a communication gap between the service providers and the patient party. The unfolding of the confrontation process creates space for and paves way for third party involvement in the conflict and negotiation process. The increasing confrontation also reflects falling trust between the service providers and the health seekers. This paper is based on information generated from a qualitative research carried out in two hospital settings in Kathmandu and Chitawan in different periods in 2019.